The effect of boron addition on the microstructure and mechanical properties of HCx tool steel - GÜLSOY, HAMİT ÖZKAN; NEVCANOĞLU, AKAY (My University, 2022)
This work handles enhancing hardness and microstructural properties of HCx tool steel owing to doping FeB. FeB was doped as boron source. Samples were prepared by using conventional powder metallurgy techniques. Samples were sintered on different conditions. While one group did not include boron, the other one had % 1.5 wt FeB. Two different sintering temperature and time were used to figure out the objective effect of boron doping. Sintered density results, hardness scores and microscope images were provided. Analyses were related to each other. The sample on best condition was detected owing to analyses. Characterization methods were executed to this sample. Analyse and characterization info revealed that was a remarkable increase on sintered density and hardness. The factors that led to this improvement were discussed.
Keywords: HCx Tool Steels; Microstructure; Hardness; Boron Doping